Pathways of Islamist adaptation: the Egyptian Muslim Brothers' lessons for inclusion moderation theory. Issue 6 (19th September 2017) - Pahwa, Sumita
ABSTRACT: The Muslim Brothers' transition from religious movement to majority-seeking party in Egypt's post 2011 democratic experiment offered a key test of the inclusion-moderation hypothesis. While the MB's increasing religious and organizational conservatism at new electoral thresholds appears to challenge the hypothesis, I argue that it was the result of strategic adaptation based on functional alternative interpretations of political opportunity that did not require a trade-off between power-seeking and expressive goals, constrained by prior pathways of electoral adaptation, and shaped by the ambiguous political incentives of democratic transition. This article shows that the MB, like other religious parties, has alternated between strategies for electoral adaptation, challenging expectations of linear evolution; that majority-seeking sometimes encourages intra-movement dynamics that are radicalizing as well as moderating; and shows that expressive goals and identity remain important to religious parties even in office, and make some paths of adaptation more attractive while precluding others. While the case affirms the relevance of political learning mechanisms predicted by inclusion-moderation theory, the divergent outcomes of this learning suggest the need to focus on the contexts and motivations that set movements along one of multiple possible adaptive pathways.